Strategi Perencanaan Pembangunan di Surabaya Dalam Pertumbuhan Ekonomi Melalui Sektor - Sektor Unggulan - Novita Maulida Ikmal; Rahma Alfiani Humairo; Aifinia Septin; Arini Hayu Pangastuti (FISIP UWP, 2020)
In development planning apart from the improvements that will be made to support the development of the city, as for economic development which is very important in planning a city development. The city of Surabaya is the capital of the province of East Java which is one of the leading sectors to help economic growth in the Surabaya area, there are 2 leading sectors, namely the trade sector and the transportation sector. Economic growth contains an overview of the process of growing and developing the economy from time to time which is always changing. Leading sectors are sectors that are able to encourage growth or development for other sectors, both sectors that supply inputs and sectors that use their outputs as inputs in the production process. Surabaya is the main trade gateway in the East Java region, so surely many industries are starting to emerge in the city of Surabaya, especially large industries that are ready to produce to meet market demands from the East Java area. As for besides the trade gate, there is also a transportation gate, the city of Surabaya. With the existence of these two sectors, the trade sector and the transportation sector in the leading sector can help in economic growth.